Odpowiedzi

2010-01-11T16:46:45+01:00
2x + 4y = 3 / -2x
3x + 6y = 5

4y = 3 - 2x / -4
3x + 6y = 5

y = 3-2x-4
3x + 6y = 5

y = -1-2x
3x + 6 * (-1-2x) = 5

y = -1-2x
3x - 6-12x = 5

y= -1-2x
-9x - 6 / +6

y= -1-2x
-9x = 5 / *(-1)

y= -1-2x
9x = -5 / 9

y = -1-2x
x = - 5/9 (ułamek)

x = 5/9 (ułamek )
y = -1-2* (-5/9)

y = -1 + 10/18
x = - 5/9

y = 4/9 (ułamek )
x = - 5/9 (ułamek )

nie wiem czy na 100% jest dobrze ale powinno być :P
2010-01-11T16:48:02+01:00
2*3+4*3=6+12=18
3*5+6*5=15+30=45
Myśle że jest dobrze